The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1037/0021-843x.99.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Pursuit gain and saccadic intrusions in first-degree relatives of probands with schizophrenia.

Abstract: Oculomotor functioning of 26 probands with schizophrenia, 12 spectrum and 46 nonspectrum first-degree relatives, and 38 nonpsychiatric control subjects was evaluated. Spectrum relatives had more anticipatory saccades (ASs) and lower pursuit gain than nonspectrum relatives, who had more ASs and lower pursuit gain than control subjects. Probands also had lower pursuit gain than nonspectrum relatives and control subjects but did not differ from other groups on AS frequency. Control subjects had more globally accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 36 publications
4
57
1
Order By: Relevance
“…Furthermore, we hypothesized an interaction between target predictability and neck torsion, with the SPNT with unpredictably moving targets being more affected. 20 healthy controls and 55 patients with neck pain participated in this experiment. Healthy controls were recruited among the hospital and university staff: they formed a heterogeneous group of 10 males and 10 females, being on average 28.4 years old (range 20-51 yr).…”
mentioning
confidence: 99%
“…Furthermore, we hypothesized an interaction between target predictability and neck torsion, with the SPNT with unpredictably moving targets being more affected. 20 healthy controls and 55 patients with neck pain participated in this experiment. Healthy controls were recruited among the hospital and university staff: they formed a heterogeneous group of 10 males and 10 females, being on average 28.4 years old (range 20-51 yr).…”
mentioning
confidence: 99%
“…Many of the nonpsychotic family members of schizophrenic patients also show poor pursuit as measured globally [29,[65][66][67], by pursuit gain [68], or by other measures [63,69]. Most studies note an association between SSP symptoms and abnormalities in aspects of smooth-pursuit eye movements [29,68,70]; one study did not find such an association [67]. These findings raised a concern that the presence of SSP symptoms may be indirectly affecting the performance in the smooth pursuit task.…”
Section: Eye Movement Abnormalitiesmentioning
confidence: 89%
“…Extensive work carried out by Holzman et al [64] and others in schizophrenic patients has shown that the measure is stable, and the findings in schizophrenia cannot be explained by disease-related factors or overt psychotic symptoms. Many of the nonpsychotic family members of schizophrenic patients also show poor pursuit as measured globally [29,[65][66][67], by pursuit gain [68], or by other measures [63,69]. Most studies note an association between SSP symptoms and abnormalities in aspects of smooth-pursuit eye movements [29,68,70]; one study did not find such an association [67].…”
Section: Eye Movement Abnormalitiesmentioning
confidence: 96%
“…6,7 We hypothesized that a similar deficit in predictive pursuit (ie, in response to only extraretinal motion signals) would occur in their relatives. Since most studies, [8][9][10] but not all, 11 noted an association between schizophrenia spectrum personality (SSP) symptoms and abnormalities in smooth pursuit eye movements, we further hypothesized that the deficit would occur mostly in relatives with SSP symptoms. Be-cause subjects with SSP are known to have subtle cognitive impairments 12 that can affect smooth pursuit performance, independent of a family history of schizophrenia, the present study recruited individuals with SSP without a known family history of psychosis as a comparison group.…”
Section: Discussionmentioning
confidence: 99%